2017
DOI: 10.3390/w9070517
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Four Nitrate Removal Kinetic Models in Two Distinct Wetland Restoration Mesocosm Systems

Abstract: Abstract:The objective of the study was to determine the kinetic model that best fit observed nitrate removal rates at the mesocosm scale in order to determine ideal loading rates for two future wetland restorations slated to receive pulse flow agricultural drainage water. Four nitrate removal models were investigated: zero order, first order decay, efficiency loss, and Monod. Wetland mesocosms were constructed using the primary soil type (in triplicate) at each of the future wetland restoration sites. Eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
(70 reference statements)
0
11
1
Order By: Relevance
“…A field-scale FTW study evaluated the removal of NO 3 -N following 17 storms throughout an establishment year and reported a median reduction of approximately 50%, which was significantly more NO 3 -N removal than the control pond (Borne et al, 2013). The NO 3 -N removal rates were likely less in that study compared to our study due to the lower NO 3 -N concentrations (~1 mg L -1 ), which have been found to reduce NO 3 -N removal rates (Messer et al, 2017c). In contrast, Winston et al (2013) found that NO 3 -N concentrations were significantly greater after implementa-tion of FTWs.…”
Section: Comparison To Past Studiescontrasting
confidence: 52%
See 2 more Smart Citations
“…A field-scale FTW study evaluated the removal of NO 3 -N following 17 storms throughout an establishment year and reported a median reduction of approximately 50%, which was significantly more NO 3 -N removal than the control pond (Borne et al, 2013). The NO 3 -N removal rates were likely less in that study compared to our study due to the lower NO 3 -N concentrations (~1 mg L -1 ), which have been found to reduce NO 3 -N removal rates (Messer et al, 2017c). In contrast, Winston et al (2013) found that NO 3 -N concentrations were significantly greater after implementa-tion of FTWs.…”
Section: Comparison To Past Studiescontrasting
confidence: 52%
“…Significant differences in DO were observed between the coffee-amended treatments (Rush Coffee, Diverse Coffee, and Control Coffee) and all other treatments (Rush, Diverse, and Control) during the Summer 1 experiment ( = 0.05). Additionally, the coffee-amended mesocosms (including Control Coffee) established ideal anaerobic conditions for denitrification within three days of experiment initiation in both the Summer 1 and Summer 2 experiments (<2 mg L -1 ; Messer et al, 2017aMesser et al, , 2017cVymazal, 2007). Lower DO concentrations have been found in other full-scale FTW evaluations (Lane et al, 2016;White and Cousins, 2013).…”
Section: Indicators Of Denitrificationmentioning
confidence: 77%
See 1 more Smart Citation
“…The authors wish to make the following corrections to this paper [1]: (1): The author name "François Bírgand" should be François Birgand. …”
mentioning
confidence: 99%
“…coefficient Ks; in particular, the error in the actual denitrification rate is about 17% when C/Ks = 0.5 and 50% when C/Ks = 1, and accounting for the decrease in the removal rate at high concentrations would yield a larger required buffer width. In a study of denitrification beds (Ghane et al, 2015) and a study of wetlands (Messer et al, 2017), a first-order model better fit nitrate removal than a zeroth-order model did. Many values of Ks in soil have been reported, including 0.5 mg/L (Kinzelbach and Schäfer, 1991), 0.89 mg/L (Killingstad et al, 2002), and 10 mg/L, which is used in three of the models reviewed by Heinen (2006a).…”
Section: Resultsmentioning
confidence: 97%